Uganda: Policies for Improved Land Management Dataset, 1999-2001 - International Food Policy Research Institute (International Food Policy Research Institute, 2004)
This survey was conducted during the Policies For Improved Land Management Project in Uganda, 1999-2003. The long term objective of the project was to contribute to improved land management in Uganda, in order to increase agricultural productivity, reduce poverty and ensure sustainable use of natural resources. The immediate purpose was to help policy makers identify and assess policy, institutional and technological strategies to improve land management. The questionnaires were administered to 107 communities, the lowest administrative units in Uganda called Local Council 1 or LC1s. The study region covered most of Uganda, including more densely populated and more secure areas in the southwest, central, eastern and parts of the north, representing seven of the nine major farming systems of the country. Within the study region, communities were selected using a stratified random sample, with the stratification based on population density and development domains defined by the different agro-ecological and market access zones. One hundred villages were selected in this way. Additional communities were purposely selected in southwest Uganda, where the African Highlands Initiative is conducting research, and in Iganga district, where the International Center for Tropical Agriculture (CIAT) is conducting research. Topics covered in the LC1 survey included community concerns and priorities, establishment and change of local council boundaries, population change, use of local council revenue, infrastructure and services, programs and organizations, land rights, and collective resource management.